THE POSITION OF SMALL AND MEDIUM TOWNS IN TOURISM DEVELOPMENT ON THE EXAMPLE OF TARNÓW - Siekierski, Jan (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article is a concise presentation of the town of Tarnów position on a tourist map of Poland. In the light of its history and general characteristics the tourist values, natural and cultural attractions of the city were discussed. Further, the tourist movement was characterized and some more important elements of tourist facilities development. The perspectives were outlined briefl y in the light of adopted strategy and directions in tourism development.